Pendampingan Pemanfaatan Hasil Sumberdaya Pertanian Untuk Menambah Pendapatan: Kras, Kabupaten Kediri, Provinsi Jawa Timur - Bambang Triyono; Abdul Haris Prawiranegara (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
The program society partnership is training abon to make banana skin at Regency. Kediri seeks to provide science and training for the creation of a new innovative product, namely banana skin, in order to create a Regency citizen effort Kediri that does not rely just on bananas. At Regency Kediri, two flaky banana producer partners are chosen to be trained in the production of banana skin raw product. Kras Village is home to two elected partners. Two, this endeavor partner does not use its banana skin until almost every day, creating banana skin flaky heaps. This software, provided by science and new to that civilization, allows banana skin to be used as a valuable commodity, called abon banana skin. Because banana skin has a high nutritional content, it is reasonable to turn it into a food product. Abon fairly to be kept up, because top abon is so much better without the bahna preservative and is enjoyed by everyone in the social circle. The society's dedication program will commence in the month of February 2020. Sort recipes and consult with partners to find a recipe to make banana skin that is long-lasting, has a genuine delight, a lovely color, and a texture that closely resembles the banana skin type at the partner effort site. It is hoped that the activity on the programs will elicit good feedback from Kediri's Regency citizens. They had a lot of fun watching this action.